phyloGenerator: an automated phylogeny generation tool for ecologists - William D. Pearse; Andy Purvis (2013)
Summary Ecologists increasingly wish to use phylogenies, but are hampered by the technical challenge of phylogeny estimation. We present phyloGenerator, an open‐source, stand‐alone Python program, that makes use of pre‐existing sequence data and taxonomic information to largely automate the estimation of phylogenies. phyloGenerator allows nonspecialists to quickly and easily produce robust, repeatable, and defensible phylogenies without requiring an extensive knowledge of phylogenetics. Experienced phylogeneticists may also find it useful as a tool to conduct exploratory analyses. phyloGenerator performs a number of ‘sanity checks’ on users' output, but users should still check their outputs carefully; we give some advice on how to do so. By linking a number of tools in a common framework, phyloGenerator is a step towards an open, reproducible phylogenetic workflow. Bundled downloads for Windows and Mac OSX, along with the source code and an install script for Linux, can be found at http://willpearse.github.io/phyloGenerator (note the capital ‘G’).